Improving draft genome contiguity with reference-derived in silico mate-pair libraries. Issue 5 (21st April 2018) - Grau, José Horacio; Hackl, Thomas; Koepfli, Klaus-Peter; Hofreiter, Michael
Abstract: Background: Contiguous genome assemblies are a highly valued biological resource because of the higher number of completely annotated genes and genomic elements that are usable compared to fragmented draft genomes. Nonetheless, contiguity is difficult to obtain if only low coverage data and/or only distantly related reference genome assemblies are available. Findings: In order to improve genome contiguity, we have developed Cross-Species Scaffolding—a new pipeline that imports long-range distance information directly into the de novo assembly process by constructing mate-pair libraries in silico . Conclusions: We show how genome assembly metrics and gene prediction dramatically improve with our pipeline by assembling two primate genomes solely based on ∼30x coverage of shotgun sequencing data.